From Album to Archive: Context, Meaning, and Two Photographic Albums from an India Mission - Murray, Sharon (Archivaria, 2008)
This article compares two nineteenth-century photographic albums: one compiled by Miss Amanda Jefferson that is now held in a private collection, and the other produced by Sir William James Wanless that is housed in a public archive. Both Jefferson and Wanless served as missionaries to Western India for the Presbyterian Church of the United States. Jefferson intended her album for public circulation and it mainly depicts the local people, compound, and women’ s domain. In his album, Wanless forwards the infrastructure and civilizing efforts of their work although his is a private album intended as an aide-mémoire. These albums exist in silent contrast to one another, each dependent on, yet obscured by, the apparent coherence and exclusivity of the other. Reading these albums together, however, can illuminate the shadows cast by each, the gaps, silences, and exclusions that result from shifting these objects between public and private spaces, both within their time and in ours. RÉSUMÉ Ce texte compare deux albums de photographies du dix-neuvième siècle : le premier a été rassemblé par Mlle Amanda Jefferson et il se trouve maintenant dans une collection privée; le second a été produit par Sir William James Wanless et il est conservé dans un centre d’archives publiques. Jef ferson et Wanless ont tous les deux servi l’Église presbytérienne des États-Unis comme missionnaires aux Indes occidentales. Jefferson s’était proposée de créer un album à dif fusion publique qui montre surtout les populations locales, les habitations et le domaine des femmes. Dans son album, Wanless fait état de l’infrastructure et des ef forts « civilisateurs » de son travail, même si son album était personnel et destiné à servir d’aide-mémoire. Ces deux albums existent en contraste l’un de l’autre, chacun ayant besoin de la cohérence apparente et de l’exclusivité de l’autre, tout en étant éclipsé en même temps par lui. La lecture des deux albums de façon parallèle, cependant, peut servir à combler les vides, les silences et les omissions qui se produisent lorsque nous déplaçons ces objets d’un espace à l’autre (soit l’espace personnel ou public), tant à leur époque qu’à la nôtre.